Thunderstorm Downbursts and Wind Loading of Structures: Progress and Prospect - Solari, Giovanni (Frontiers in Built Environment, 2020)
In 1961, Davenport published a paper, considered by most to be a critical work in the study of wind engineering, in which meteorology, micrometeorology, climatology, aerodynamics, and structural dynamics were embedded in a homogeneous framework of the wind loading of structures. This framework, known as Davenport chain and based on a wind model coherent with synoptic-scale extra-tropical cyclones, is so limpid as to become a sort of axiom. In 1977, Gomes and Vickery separated thunderstorm from non-thunderstorm winds, evaluated their extreme wind speed marginal distributions, and from them obtained a mixed statistical model later generalized to other wind types. This viewpoint, dealt with as a milestone in the emerging issue of mixed climatology, pointed out the difficulty of labeling a heterogeneous set of phenomena endowed with different velocity fields, frequencies, durations, and sizes by the generic term “wind.” Many wind types, in particular tropical cyclones, tornadoes, and downslope winds are typical of limited and well-known areas. Extra-tropical depressions and thunderstorms are natural hazards that affect the whole planet. This paper provides a state-of-the-art discussion of thunderstorm downburst, one of the most spectacular and damaging events caused by nature, and its wind loading of structures. Also, in light of the planet's climatology evolution, this topic is a key issue of structural safety and sustainability.